2018
DOI: 10.5858/arpa.2017-0184-ra
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Testing of Non–Small Cell Lung Carcinoma Diagnosed by Endobronchial Ultrasound–Guided Transbronchial Fine-Needle Aspiration: The Cleveland Clinic Experience

Abstract: Context.— Given the increasing demand for molecular testing of non–small cell lung carcinoma specimens to guide therapeutic decision-making and the trend toward minimally invasive techniques for obtaining diagnostic tissue, cytopathology laboratories must devise strategies to maximize DNA yield for necessary molecular testing. Objective.— To describe our experience at Cleveland Clinic with epidermal growth factor receptor (EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Endobronchial ultrasound transbronchial needle aspiration (EBUS-TBNA) sampling of lymph nodes has become an important alternative for obtaining material for next-generation sequencing (NGS) for lung cancer [1-3]. Detailed mutation profiling is expected to benefit patient management by enabling therapy against targetable somatic mutations [4-7].…”
Section: Introductionmentioning
confidence: 99%
“…Endobronchial ultrasound transbronchial needle aspiration (EBUS-TBNA) sampling of lymph nodes has become an important alternative for obtaining material for next-generation sequencing (NGS) for lung cancer [1-3]. Detailed mutation profiling is expected to benefit patient management by enabling therapy against targetable somatic mutations [4-7].…”
Section: Introductionmentioning
confidence: 99%
“…Cytologic samples provide high‐quality DNA for molecular testing and are comparable, or even superior to, formalin‐fixed, paraffin‐embedded surgical pathology specimens for the evaluation of clinically relevant mutations . Liquid‐based cytology (LBC) makes it possible to perform additional techniques, such as immunocytochemistry and in situ hybridization, and also allows for molecular testing using DNA and RNA extracted from the remaining fixed cells . Some studies have demonstrated that LBC systems provide excellent cell preservation for routine cytopathology and can be used for DNA‐ and RNA‐based molecular testing …”
Section: Introductionmentioning
confidence: 99%
“…4,5 Liquid-based cytology (LBC) makes it possible to perform additional techniques, such as immunocytochemistry and in situ hybridization, and also allows for molecular testing using DNA and RNA extracted from the remaining fixed cells. [4][5][6] Some studies have demonstrated that LBC systems provide excellent cell preservation for routine cytopathology and can be used for DNA-and RNAbased molecular testing. 4,5 The 2015 World Health Organization classification 7 classifications.…”
mentioning
confidence: 99%
“…Wei et al described using residual PreservCyt (Cytyc Corporation, Marlborough, Massachusetts) specimens from FNA samples and body fluids (either fresh unconcentrated specimens or residual PreservCyt specimens) to extract DNA for multigene NGS analysis . A recent study has described using residual CytoLyt (Hologic Inc, Marlborough, Massachusetts) from endobronchial ultrasound–guided transbronchial needle aspirates for evaluation using NGS . Similarly, another study has reported that the postcentrifuged supernatant fluid from FNA samples combined with the residual PreservCyt yields adequate DNA for mutational analysis by NGS …”
mentioning
confidence: 99%